The Economics of Healthy Ageing in China - Almas Heshmati (Institute for the Study of Labor (IZA), 2016)
Healthy ageing is a challenge for many countries with significant shares of elderly people. Literature refers to China's ageing population as a ticking time bomb which paradoxically is both a challenge and an opportunity for the country. Health is considered an important determinant of economic growth and competitiveness. The health of the elderly population determines its need for resources and care. Thus, investing in healthy ageing contributes to economic and social well-being. This study is a review of literature on the social and economic aspects of healthy ageing. It summarizes alternative approaches presented in literature to ease pressures of a rapidly growing ageing population. The main focus is on strategies for healthy ageing, policy practices and measures, organization, finances and manpower resources to promote healthy ageing in China. Up-to-date theories and methods applied to household surveys and population statistics are used to quantify the problem, resource requirements and estimating the social and economic benefits of having policies and measures for healthy ageing. Conclusions are drawn with respect to conditions of healthy ageing in China and about the state policy in this regard.
Keywords: H75; I15; I18; I38; P36; 330; healthy ageing; ageing in China; active ageing; challenges and opportunities; economics of healthy ageing